2008
DOI: 10.1111/j.1600-0463.2008.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Alloiococcus otitidis—otitis media pathogen or normal bacterial flora?

Abstract: During the last decade a new potential otitis media pathogen, Alloiococcus otitidis, has been studied. It is still not clear whether this bacterium really is a pathogen, although it has been found in a high percentage of middle ear effusions in children. The present study aimed to investigate the presence of A. otitidis in the nasopharynx and outer ear canals, and to develop a culture method that would make it possible to isolate A. otitidis from these locations. Nasopharyngeal samples (n = 129) from children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 19 publications
4
48
0
3
Order By: Relevance
“…There has been debate about whether members of the bacterial genus Alloiococcus play a role in the pathogenesis of otitis media in children or if they are part of the commensal microbiota (61,62). Using molecular techniques, we found higher relative abundance in CSOM patients with cholesteatoma than in controls or other subject groups.…”
Section: Discussionmentioning
confidence: 56%
“…There has been debate about whether members of the bacterial genus Alloiococcus play a role in the pathogenesis of otitis media in children or if they are part of the commensal microbiota (61,62). Using molecular techniques, we found higher relative abundance in CSOM patients with cholesteatoma than in controls or other subject groups.…”
Section: Discussionmentioning
confidence: 56%
“…These facts, in combination with a very mild reaction in the middle ears of rats reported by Tano et al [19], suggest that A. otitidis is commensal and a part of the normal bacterial flora in the outer ear canals. However, it is possible that A. otitidis translocated to middle ear canals or combination with other bacterial flora could induce an inflammation causing acute otitis.…”
Section: Discussionmentioning
confidence: 86%
“…Although A. otitidis has been recovered from the middle ear of children with acute otitis media, recent studies showed that A. otitidis was frequently found in the outer ear canals of healthy volunteers [17][18][19]. These facts, in combination with a very mild reaction in the middle ears of rats reported by Tano et al [19], suggest that A. otitidis is commensal and a part of the normal bacterial flora in the outer ear canals.…”
Section: Discussionmentioning
confidence: 92%
“…The recovery rate of A. otitidis from MEEs of children with OME has been up to 5% by culture and up to 50% by PCR [7,8]. It was considered as an important middle ear pathogen after its first recovery from OME, but its etiological role in OME has been doubted in more recent studies [11,24]. Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%